Biomechanical load quantification of national and regional soccer players with an inertial sensor setup during a jump, kick, and sprint task: assessment of discriminative validity - Bastiaansen, B. J. C.; Vegter, R. J. K.; Wilmes, E.; de Ruiter, C. J., Goedhart, E. A.; Lemmink, K. A. P. M.; Brink, M. S. (Sports Engineering, 2024)
Training load quantification methods may help optimize soccer performance. However, whole-body indicators potentially underestimate biomechanical load. A new inertial sensor setup allows joint-specific biomechanical load quantification. Good discriminative validity further supports the use of this method, and therefore the purpose of this study is to assess the discriminative validity of this method during soccer-specific activities. Twelve national and sixteen regional soccer players wore an inertial sensor setup and performed countermovement jumps, soccer kicks, and 30 m sprints. Between-group differences in angular acceleration-based biomechanical load indicators Knee Load, Hip Load, and performance were assessed using MANOVAs and Cohen`s effect sizes. Furthermore, relationships with performance were explored. National players showed higher Knee Load during jumping (mean difference: 0.11 A.U., ES = 0.93, p = 0.02), kicking (mean difference: 1.94 A.U., ES = 0.94; p = 0.02), and almost during sprinting (mean difference: 12.85, ES = 0.77; p = 0.05). Hip Load did not differ between groups across all tasks, although national players outperformed regional players on all tests. Significant relationships between Knee Load (rjump = 0.41, rkick = 0.65), Hip Load (rjump = 0.42), and performance were observed with 95% confidence intervals ranging from trivial to large. The results confirm discriminative validity of Knee Load for jumping and kicking, but not for sprinting and Hip Load in general. The confidence intervals of the established relationships suggest that the biomechanical loads might not entirely explain between-group differences in performance. The results can be used as reference values for biomechanical load quantification in the field.